Review paper: properties of low molecular weight phenol formaldehyde – treated bamboo composite - Hien Mai, Trinh; Thi Tham, Nguyen; Tat Thang, Nguyen; Thi Yen, Nguyen; Huyen, Nguyen Van; Thi Kim Hong, Tang (Journal of Forestry Science and Technology, 2023)
Impregnation of bamboo in phenol formaldehyde (PF) solution is one of the promising solutions to overcome the drawback of the material. The use of low molecular weight PF resin (LMW PF) in the production of bamboo composite materials not only improves the dimensional stability but also increases the mechanical strength of the material. The bonding interface between bamboo elements and adhesives is presumed to be significantly influenced by the degree of adhesive penetration into the porous network of interconnected cells of bamboo surfaces. The permeation of PF resins in bamboo is closely related to their molecular weight. LMW PF resin will overpenetrate and lead to an undesirable starved bondline while high-MW PF resins only remain in the bondline and it is difficult to form mechanical interlocking. This paper discusses the research results on the bonding quality of bamboo strips when impregnated in LMW PF solution with different ratios and different pressing technology parameters; at the same time, physical and mechanical properties of bamboo composite materials treated with PF PTLT such as: water absorption resistance, dimensional stability, bonding strength, modulus of rupture (MOR), modulus of elasticity (MOE) are also significantly improved. This is a scientific basis that can serve as a premise for the research on technology to produce composite materials from bamboo and LMW PF in Vietnam.